PARTICULARITIES ON THE REGULATION OF THE SUE PETITION, IN THE LIGHT OF PRACTICAL DIFFICULTIES AND LEGISLATIVE CHANGES - Andrei-Radu DINCĂ (Challenges of the Knowledge Society)
According to the Romanian Civil Procedure Code, one of the trial stages of first instance is represented by the written stage in which, as a general rule, the fulfillment of the requirements regarding the petition content is analysed. This stage is a novelty of the new Civil Procedure Code. The purpose of this check is to prevent the introduction of an inform application, as well as for predictability reasons, in order to guarantee the other parties the right of defend oneself, in order to be able to effectively respond to the plaintiff’s claims. However, the institution has experienced some interpretation and enforcement difficulties, but also legislative changes that will be the subject of our analiysis.